Loss of corneal nerves and brain volume in mild cognitive impairment and dementia. Issue 1 (5th April 2022) - Ponirakis, Georgios; Hamad, Hanadi Al; Khan, Adnan; Petropoulos, Ioannis N.; Gad, Hoda; Chandran, Mani; Elsotouhy, Ahmed; Ramadan, Marwan; Gawhale, Priya V.; Elorrabi, Marwa; Gadelseed, Masharig; Tosino, Rhia; et al.
Abstract: Introduction: This study compared the capability of corneal confocal microscopy (CCM) with magnetic resonance imaging (MRI) brain volumetry for the diagnosis of mild cognitive impairment (MCI) and dementia. Methods: In this cross‐sectional study, participants with no cognitive impairment (NCI), MCI, and dementia underwent assessment of Montreal Cognitive Assessment (MoCA), MRI brain volumetry, and CCM. Results: Two hundred eight participants with NCI (n = 42), MCI (n = 98), and dementia (n = 68) of comparable age and gender were studied. For MCI, the area under the curve (AUC) of CCM (76% to 81%), was higher than brain volumetry (52% to 70%). For dementia, the AUC of CCM (77% to 85%), was comparable to brain volumetry (69% to 93%). Corneal nerve fiber density, length, branch density, whole brain, hippocampus, cortical gray matter, thalamus, amygdala, and ventricle volumes were associated with cognitive impairment after adjustment for confounders (All P 's < .01). Discussion: The diagnostic capability of CCM compared to brain volumetry is higher for identifying MCI and comparable for dementia, and abnormalities in both modalities are associated with cognitive impairment.